Performance analysis of poultry feed marketers in Delta State, Nigeria - Gbigbi, Theophilus Miebi; Chuks-Okonta, V.A.A. (International journal of Rural Development, Environment and Health Research, 2020)
This study examined the performance of poultry feed marketers in the Delta State in order to increase investments by potential investors in the enterprise which is economically viable. Delta State has been chosen for the study due to its high concentration of marketers in poultry feed. A sample of 75 poultry feed marketers were randomly selected from the markets in the study area. Data were collected using structured questionnaire and analyzed using descriptive statistics, multiple regression techniques and cost and return analysis. The mean age of marketers was 45years. Majority (57%) were males. About 64% were literate with 12 years of marketing experience. The mean household size was 6 persons. The mean bags sold daily was 3.3. Marketers sell different types of poultry feeds. The most common marketing channel was producer-wholesale-retailer-consumer. The regression results showed that buying price of the poultry feed, cost of transportation, market charges and cost of shop was negatively and significantly associated with profit while selling price, marketing experience and quantity sold showed a positive relationship with profit. The enterprise proved profitable with significant gross margin and marketing efficiency level of N51,181.87 and 81.6% respectively. The major constraints to poultry feed marketing were inadequate credit facility, transportation, insufficient market information and price fluctuation. It is recommended that credit facilities should be provided to the feed marketers to ease purchase of inputs. To further reduce the cost of initial purchase, the government and other agencies should consider subsidizing poultry feed.